HUBUNGAN BEBAN PERAWATAN CAREGIVER TERHADAP JENIS KELAMIN DAN USIA PADA PASIEN SKIZOFRENIA YANG BEROBAT JALAN DI RSJ. PROF. DR. M. ILDREM MEDAN - BAITUL AMANAH; NANDA SARI NURALITA (LP2MTBM MAKARIOZ, 2022)
Schizophrenia is one of the most common psychotic disorders in the world. Schizophrenia patients in leading an optimaldaily life, needed the help in caring for and support from other parties called Caregiver. Caregiver as a treatment systemoutside the hospital often experiences the burden of providing optimal services in the social needs of patients. The burdenexperienced by caregiver refers to the burden of care, social, psychological, behavioral, functional, medical, physical andfinancial. This study aims to determine the correlation between caregiver care burdens on sex and age in schizophrenicpatients who are on outpatient care at RSJ Prof. Dr. M. Ildrem which was held from August to December 2016. Categoricalanalytic using cross sectional design. ZBI data obtained from 80 samples were then analyzed using the Chi-Square test. Chi-Square test results showed that there was a relationship between caregiver care burden and sex of schizophrenic patientswith a P value = 0.001 (p <0.05). And there is a relationship between caregiver care load and age of schizophrenia patientswith p value = 0.01 (p <0.05). The burden of caregiver care has a significant influence on the sex and age of schizophrenicpatients.